Monitoring Surface Water Quality of Asi River During the 2006 Muslim Sacrifice Holiday - GOKSEL OZDILEK, HASAN; KEMAL SANGUN, MUSTAFA (Asian Journal of Chemistry, 2010)
In 2006, the last 90 km of the river (Turkish part only) is studied in terms of water quality during the Sacrifice Holiday that was observed on January 10-14. With respect to time, trace metal concentrations, in general, were found to decline but an increase in metal flux due to rise in river flow occurred.